A single‐shot T2 mapping protocol based on echo‐split gradient‐spin‐echo acquisition and parametric multiplexed sensitivity encoding based on projection onto convex sets reconstruction. Issue 1 (7th May 2017) - Chu, Mei‐Lan; Chang, Hing‐Chiu; Oshio, Koichi; Chen, Nan‐kuei
Abstract : Purpose: To develop a high‐speed T2 mapping protocol that is capable of accurately measuring T2 relaxation time constants from a single‐shot acquisition. Theory: A new echo‐split single‐shot gradient‐spin‐echo (GRASE) pulse sequence is developed to acquire multicontrast data while suppressing signals from most nonprimary echo pathways in Carr‐Purcell‐Meiboom‐Gill (CPMG) echoes. Residual nonprimary pathway signals are taken into consideration when performing T2 mapping using a parametric multiplexed sensitivity encoding based on projection onto convex sets (parametric‐POCSMUSE) reconstruction method that incorporates extended phase graph modeling of GRASE signals. Methods: The single‐shot echo‐split GRASE‐based T2 mapping procedure was evaluated in human studies at 3 Tesla. The acquired data were compared with reference data obtained with a more time‐consuming interleaved spin‐echo echo planar imaging protocol. T2 maps derived from conventional single‐shot GRASE scans, in which nonprimary echo pathways were not appropriately addressed, were also evaluated. Results: Using the developed single‐shot T2 mapping protocol, quantitatively accurate T2 maps can be obtained with a short scan time (<0.2 seconds per slice). Conclusion: Accurate T2 mapping with minimal signal contamination from CPMG high‐order echo pathways can be achieved by the developed method that integrates single‐shot echo‐split GRASE acquisition and parametric‐POCSMUSE reconstruction. Magn Reson Med 79:383–393, 2018. © 2017 International Society for Magnetic Resonance in Medicine.